1981
DOI: 10.1002/clc.4960040404
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of ventricular fibrillation or cardiac arrest in patients hospitalized for acute myocardial infarction

Abstract: A community-wide study of patients hospitalized with acute myocardial infarction in metropolitan Baltimore was conducted to examine socio-demographic and clinical characteristics in association with ventricular fibrillation and cardiac arrest (VF/CA). Multivariate analyses revealed that variables significantly associated with occurrence of VF/CA included older age (60 years or older), male sex, and a history of cigarette smoking. These factors allow the identification of subgroups of patients hospitalized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Identification of simply assessed clinical variables associated with subsequent ventricular tachycardia (VT) and ventricular fibrillation (VF) could prove useful in the triage of patients to more aggressive pharmacologic-or device-based therapies. Previous observational studies have demonstrated that traditional cardiac risk factors, such as age, hypertension, and tobacco use, are associated with an increased risk of VT/VF after MI (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of simply assessed clinical variables associated with subsequent ventricular tachycardia (VT) and ventricular fibrillation (VF) could prove useful in the triage of patients to more aggressive pharmacologic-or device-based therapies. Previous observational studies have demonstrated that traditional cardiac risk factors, such as age, hypertension, and tobacco use, are associated with an increased risk of VT/VF after MI (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiologic risk factors associated with ventricular arrhythmia have been observed (3)(4)(5). Risk factor assessment is ever-changing as modern pharmacologic therapy for coronary artery disease and heart failure change (25).…”
Section: Jaccmentioning
confidence: 99%
“…A recent multivariate study identified age, sex, and smoking as the most important variables for late cardiac arrest. 39 Because the important prognostic variables are identical to clinically important variables, the time of discharge could be determined by the presence or absence of these variables alone. However, our proposed model can quantitate the risk for an individual patient based on a combination of important variables for three end points.…”
Section: Discussionmentioning
confidence: 99%